The social functions of intergroup schadenfreude - Yam, P (2017)
Schadenfreude is a German word, which describes the pleasure that people take in someone else’s misfortune. The aim of the present research was to investigate the social functions of intergroup schadenfreude. Chapter 2 presents Studies 1 – 3, focusing on the social functions of experiencing intergroup schadenfreude in the context of football tournaments, using both concurrent and retrospective methods. Study 1 did not find any relation between change in perceived relative status and intergroup schadenfreude, possibly because of the sample’s low domain interest and identification. However, schadenfreude was positively associated with change in status in Study 2 and with change in performance evaluation in Study 3 as expected. Also, across all three studies, intergroup schadenfreude was associated with consequences corresponding to its social distancing (e.g., distance from or dislike of the outgroup and intention to humiliate its members) and social affiliation functions (e.g., intention to celebrate with ingroup members). Importantly, schadenfreude mediated the effects of change in status (Study 2) and performance evaluation (Study 3) on these consequences. Chapter 3 presents Studies 4 and 5, which investigated whether social status is specifically associated with intergroup schadenfreude, and examined whether this social concern helps to differentiate intergroup schadenfreude from victorious joy (i.e., happiness about a third-party’s victory). I developed a new experimental paradigm to manipulate participants’ concern for status to elicit feelings of intergroup schadenfreude. I also manipulated participants’ concern for external rewards associated with the third-party’s victory to prompt victorious joy. However, in both studies, the concern for external rewards was the main influence on both intergroup schadenfreude and victorious joy, although a multivariate interaction between the two motives affected these emotions in Study 4. Hence, these studies suggest that status may be only one of the many motives underlying intergroup schadenfreude. Chapter 4 presents Study 6, which was a vignette-based study investigating the social affiliation functions of sharing intergroup schadenfreude as a function of ingroup identification. Participants read tweets from an ingroup member expressing either intergroup schadenfreude or victorious joy. Identification was also manipulated. However, results showed that recipients of intergroup schadenfreude messages formed more negative impressions of the tweeter and intended to distance themselves from him/her more than recipients of victorious joy messages. Chapter 5 provides an overview of the findings, contributions, and limitations of these six studies and discusses directions for future research. Overall, this thesis went beyond the current focus on the antecedents of schadenfreude and took steps towards the development of a social-functional account of intergroup schadenfreude.